Laudos arbitrales y la restitución de relaciones contractuales de contratos de obra en supuestos de continuación/culminación de la obra por tercero - Rivas Caso, Gino (2016)
¿Does an award that restitutes a, wrongly resolved, construction contract have effects if the project of work is completed? And ¿what effects does an award have if the work is being developed by a third party?.In this article, the author seeks to answer the questions raised exposing what effects has, in the reality, an award that reinstates contractual relations.